(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless Sensor Network (WSN) has gained tremendous research attention recently due to their extensive applications. As sensor nodes being battery operated, many researchers have made attempts to prolong the lifespan of the WSN by reducing the-per node energy consumption and efficiently utilizing the sensor nodes. Since the sensors operate on battery of limited power, it is a great challenging aim to design an energy efficient routing protocol, which can minimize the delay while offering high-energy efficiency and long span of network lifetime. This is the survey on different deployment schemes on irregular geographical target area, we propose to include the concept of voronoi diagram based approach in WSNs, to provide a way of dividing an irregular geographical area into a number of regular regions. In this regions, we deployed sensor nodes, among all these nodes CH(cluster head) is selected based on residual energy level of sensor nodes in a cluster. Then fused data of CH will be transmitted to sink node through multihop routing.